An Analysis of the Short-Run Consumer Demand for Gasoline Using Household Survey Data: A Reply - Archibald, Robert; Gillingham, Roger (The Review of Economics and Statistics, 1983)
Robert Archibald, Roger Gillingham, An Analysis of the Short-Run Consumer Demand for Gasoline Using Household Survey Data: A Reply, The Review of Economics and Statistics, Vol. 65, No. 3 (Aug., 1983), pp. 533-534